Pengaruh Keberagaman Dewan Direksi Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur - Nafisa Rokhilla Haris Lubis; Syahyunan Syahyunan; Muhammad Fauzan Azhmy (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
This study aims to determine the effect of the diversity of the board of directors on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. This research is causal associative research and the type of data used is quantitative data. The data used are obtained from audited company financial reports and annual reports from manufacturing companies listed on the Indonesia Stock Exchange. The analytical method used is descriptive analysis and multiple linear regression of panel data. The population of this study are manufacturing companies for the 2015-2019 period, which totaled 181 companies. The sample in this study amounted to 28 companies. The results of this study indicate that gender diversity has a negative and insignificant effect on financial performance, national diversity has a negative and significant effect on financial performance, age diversity has a positive and insignificant effect on financial performance, and educational diversity has a negative and insignificant effect on financial performance. The diversity of gender, nationality, age and education simultaneously has a positive and significant effect on financial performance.